Exploring the pandemic from feminist research: social scientists, covid and university - Alonso, María; Mendoza, Diego; Espinosa, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research aims to understand the impact of the COVID-19 pandemic on the research processes of women social scientists at the University of Granada from a gender perspective. We have also explored strategies that the researchers have developed to continue their studies. Some of these strategies have been conceived as care practices in research. On the other hand, we have collected proposals aimed at improving research practice in times of pandemic. In order to address these objectives, we have implemented a qualitative methodology based on in-depth interviews and feminist epistemological and methodological perspectives.